Multidimensional indicator to measure quality in education (2021)
In this research, a multidimensional indicator to measure quality in education in public high schools is proposed. In the study, carried out in the Atlántico region in Colombia, the initial step was to identify the factors that directly affect education quality through databases and teacher surveys. Then, statistical analysis was performed through multiple regression to develop an equation of weighted factors, based on the quantification of each factor's importance in influencing education quality, allowing the identification of the most relevant factors. Additionally, a quality measurement methodology is proposed based on categorizing the most critical factors into extrinsic and intrinsic factors, obtaining a consistent result with the conditions at each school. The results of the study demonstrate the relevance of extrinsic factors, mainly the social context. Such results imply that beyond the activities performed to strengthen classroom teaching, the social component is a crucial factor to improve education quality and that variables such as extracurricular activities support the students' integral formation and positively impact their academic performance. © 2022